Influences on a Culture that Supports Organ Donation After Circulatory Death. (July 2018) - Milross, Luke A; O'Donnell, Thomas; Bucknall, Tracey K; Pilcher, David V; Ihle, Joshua F
Introduction: Organ donation remains rare, particularly in Australia where various initiatives attempt to bolster donation rates including a renewed interest in Donation after Circulatory Death (DCD). DCD reintroduction has been accompanied by increased donor numbers and organs transplanted, with associated favourable short- and long-term transplant outcomes. However, reintroduction has been met with variable institutional and individual support. Ethical concerns are often raised, particularly surrounding how a clinician's decision to palliate and withdraw cardiopulmonary support may be influenced by the desire for DCD. The current study aims for a greater understanding of DCD perceptions among staff involved. Materials and Methods: This qualitative study utilised semi-structured interviews with intensive care staff at the Alfred Hospital ICU in Melbourne. Staff participants were recruited through email invitation, and a trained interviewer used a semi-structured interview guide to explore perceptions surrounding DCD. Twelve staff participants were interviewed based on reaching a data saturation point. Several 10-point Likert scales were included. Interviews were digitally recorded and transcribed verbatim for thematic analysis. Results: Twelve participants were interviewed; eight intensive care physicians, three donation coordinators and one bedside nurse. Responses to the Likert scale questions were averaged (n=12). Donation after brain death was unanimously accepted (Average=10.0), whereas DCD acceptance was lower but remained supported (Average=8.8). Interview responses generated five themes, each containing subthemes. Themes included: 1) Logistical and circumstantial obstacles surrounding DCD implementation; 2) Cultural and environmental influences on DCD decision making; 3) Influence of personal factors on DCD implementation; and 4) Influence of families of potential donors on DCD. Discussion: Respondents had concerns with DCD where perceptions existed that DCD would increase family distress, either from timeframes not being met or logistical delays. A second major source of concern stemmed from personal conflict relating to their role. There was difficulty transitioning from primarily sustaining life or facilitating palliation alone to advocating for DCD, especially where there was perceived potential for deviations from standard palliation in analgesia, sedation and investigations. Overall, concerns were overcome by reliance on a supportive work environment, rationalisation of concerns over time and reliance on protocols. Conclusion: A supportive culture within the Alfred Hospital ICU meant DCD occurred with minimal institutional resistance. However, some individual concerns surrounding DCD were identified. These may be present and amplified in other centers. More study is required in centers where institutional resistance to DCD is identified that DCD may be further promoted to expand the donor pool.